Association between humoral immunity and clinical outcomes of patients after out-of-hospital cardiac arrest and resuscitation: a retrospective study - Zhenyu Shan; Xingsheng Wang; Le An; Chenchen Hang; Zihao Jiang; Weijie Cheng; Ziqi Zhong; Rui Shao; Ziren Tang (BMC Emergency Medicine)
Abstract Background Patients with out-of-hospital cardiac arrest (OHCA) suffer from hypoxia-ischemia and ischemia-reperfusion injury (IRI) after the return of spontaneous circulation (ROSC). The impact of early humoral immunity on prognosis in this process remains unclear. Methods Outcomes at discharge were evaluated in 183 patients resuscitated from OHCA, including neurological outcomes as measured by CPC scores, survival, and length of stay (LOS). Humoral immunity, including IgG, IgA, IgM, C3, and C4, was tested on the first day of admission. Difference test, restricted cubic spline, and correlation analysis were used to analyze the correlation between humoral immunity and outcomes. Results Differences were observed in IgM, C3, and C4 levels among patients with different prognoses. Patients with poor prognosis have lower IgM levels (CPC 1–2 vs. CPC 3–5: 68.3[47.05–105] vs. 55.45[31.95–86.12] mg/dL, P = 0.0256), lower C3 levels (CPC 1–2 vs. CPC 3–5: 72.1[62.6–72.1] vs. 63.05[49.83–79.72] mg/dL, P = 0.0091; survival vs. dead: 72.1[60.9-86.62] vs. 58.7[43.7–72.6] mg/dL, P < 0.0001), and lower C4 levels (survival vs. dead: 18.9[15.38–22.92] vs. 17.2[11.85–21.5] mg/dL, P = 0.0148). Non-linear correlations were found between humoral immunity and prognosis (IgM: ORnon−linear=1.068[95%CI: 1.009–1.130], Pnon−linear=0.0236); C3: ORnon−linear=1.048[95%CI: 1.000-1.097], Pnon−linear=0.0488). LOS was negatively linearly correlated with IgG (R2 adjusted = 0.115, P = 0.0148) and C3 (R2 adjusted = 0.127, P = 0.0108) in patients with CPC 1–2. Conclusions Humoral immunity is at a low level in OHCA patients after ROSC, and humoral immunity was associated with neurological prognosis, survival at discharge, and LOS.